Superblock Urbanism in Dhaka as a Sustainable Redevelopment Strategy for Tejgaon Industrial Area - Raj, Shahriar Iqbal; Wasif, Tajwar Hossain; Ahsan, Mujtaba; Anik, AKM Saleh Ahmed (Alanya Üniversitesi, 2025)
Dhaka’s rapid urbanisation has intensified challenges of fragmented land use, congestion, and environmental decline, particularly in the Tejgaon Industrial Area (TIA), once designated for light industry but now marked by unregulated mixed-use growth. This study examines the superblock model as a sustainable redevelopment framework for TIA, aiming to integrate density management, mobility, and environmental resilience. A mixed-methods approach combined GIS-based spatial analysis, traffic observations, policy review of the Detailed Area Plan (2022–2035) and Building Construction Rules (2008), and participatory design workshops. Insights from 151 residents, workers, and students informed scenario testing across three models: plot-based, block-based, and superblock development. Findings show that superblocks reduce congestion by diverting traffic to peripheral roads, enhance permeability with 44% more permeable surfaces compared to block-based schemes, and allocate nearly 50% of land for open and public spaces. These outcomes highlight the potential of superblock urbanism to support Sustainable Development Goals (SDGs 3, 11, 13, and 15), improving walkability, public health, and climate resilience. The study concludes that superblocks provide a scalable planning strategy for Dhaka’s transformation and for other fast-growing urban contexts.